10th International Conference on Practical Applications of Computational Biology & Bioinformatics - Saberi Mohamad, Mohd.; Rocha, Miguel P.; Fdez-Riverola, Florentino; Domínguez Mayo, Francisco J.; De Paz, Juan F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Biological and biomedical research are increasingly driven by experimental techniques that challenge our ability to analyse, process and extract meaningful knowledge from the underlying data. The impressive capabilities of next generation sequencing technologies, together with novel and ever evolving distinct types of omics data technologies, have put an increasingly complex set of challenges for the growing fields of Bioinformatics and Computational Biology. The analysis of the datasets produced and their integration call for new algorithms and approaches from fields such as Databases, Statistics, Data Mining, Machine Learning, Optimization, Computer Science and Artificial Intelligence. Clearly, Biology is more and more a science of information requiring tools from the computational sciences. In the last few years, we have seen the surge of a new generation of interdisciplinary scientists thathave a strong background in the biological and computational sciences. In this context, the interaction of researchers from different scientific fields is, more than ever, of foremost importance boosting the research efforts in the field and contributing to the education of a new generation of Bioinformatics scientists. PACBB'16 hopes to contribute to this effort promoting this fruitful interaction. PACBB'16 technical program included 21 papers spanning many different sub-fields in Bioinformatics and Computational Biology. Therefore, the conference will certainly promote the interaction of scientists from diverse research groups and with a distinct background (computer scientists, mathematicians, biologists). The scientific content will certainly be challenging and will promote the improvement of the work being developed by each of the participants.
Data And Text Mining -- Gene Expression -- Genomics -- Systems Biology.
Keywords: Computational intelligence; Artificial intelligence; Bioinformatics; Computational Intelligence; Artificial Intelligence; Computational and Systems Biology